How tree decline varies the anatomical features in Quercus brantii - Soheili, Forough; Abdul-Hamid, Hazandy; Almasi, Isaac; Heydari, Mehdi; Tongo, Afsaneh; Woodward, Stephen; Naji, Hamid Reza (Multidisciplinary Digital Publishing Institute, 2023)
Drought has serious effects on forests, especially semi-arid and arid forests, around the world. Zagros Forest in Iran has been severely affected by drought, which has led to the decline of the most common tree species, Persian oak (Quercus brantii). The objective of this study was to determine the effects of drought on the anatomical structure of Persian oak. Three healthy and three declined trees were sampled from each of two forest sites in Ilam Forest. Discs were cut at breast height, and three sapwood blocks were taken near the bark of each tree for sectioning. The anatomical characteristics measured included fiber length (FL), fiber wall thickness (FWT), number of axial parenchymal cells (NPC), ray number (RN), ray width (RW), and number of calcium oxalate crystals. Differences between healthy and declined trees were observed in the abundance of NPC and in RN, FL, and FWT, while no differences occurred in the number of oxalate crystals. The decline had uncertain effects on the FL of trees from sites A and B, which showed values of 700.5 and 837.3 μm compared with 592.7 and 919.6 μm in healthy trees. However, the decline resulted in an increase in the FWT of trees from sites A and B (9.33 and 11.53 μm) compared with healthy trees (5.23 and 9.56 μm). NPC, RN, and RW also increased in declined individuals from sites A and B (28.40 and 28.40 mm−1; 41.06 and 48.60 mm−1; 18.60 and 23.20 μm, respectively) compared with healthy trees (20.50 and 19.63 mm−2; 31.60 and 28.30 mm−2; 17.93 and 15.30 μm, respectively). Thus, drought caused measurable changes in the anatomical characteristics of declined trees compared with healthy trees.